Sistem Pengendalian Lampu Ruangan Menggunakan Sumber Energi Panel Surya Berbasis IoT (Internet of Thing) - Faritcan Siallagan, Timbo; Susanti, Eka (Jurnal Manajemen Sistem Informasi (JMASIF), 2023)
Efficient use of energy is emphasized in the use of electronic equipment. It aims to create an environmentally friendly technology. No exception for lighting in homes, buildings, schools and so on. Often, we see many room lights that turn on when not in use. This can be a huge waste of electricity. For this reason, a solution to this problem is needed, so an energy-efficient automatic lamp is needed. This lighting system aims to adjust the lighting conditions automatically based on the surrounding conditions. This system will detect the brightness or dimness of a room. If the room is bright enough, the light will turn off. However, when the room is dark, the lights will automatically turn on. The main energy source for this lamp is not from PLN electricity, but from solar panels. The use of solar panels aims to save electricity from PLN and utilize energy sources that are free and available for a very long time. This solar panel-based lighting system is already running well. This system is already able to utilize energy from the sun through solar panels to charge the battery, and the output of the system is that the lights are controlled automatically by the sensor block according to environmental conditions.